2008
DOI: 10.1016/j.jasms.2008.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Using fluorescence dyes as a tool for analyzing the MALDI process

Abstract: In a recent paper (Setz, P. D.; Knochenmuss, R. Phys. Chem. A 2005, 109, 4030 -4037) energy-transfer from excited matrix molecules to fluorescent traps was used to study the role of pooling reactions for the ionization processes in matrix-assisted laser desorption ionization (MALDI) using 2,5-dihydroxybenzoic acid as matrix. Exciton trapping was shown to interfere with matrix ionization. These investigations were extended to analyze the influence of fluorescent traps on both matrix and analyte ions for ␣-cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Device parameters were set to identical values as given in [22]. The delayed extraction (DE) time was varied from 10 ns (shortest selectable interval) to 1000 ns in 200 ns steps.…”
Section: Measurement Of the Initial Ion Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…Device parameters were set to identical values as given in [22]. The delayed extraction (DE) time was varied from 10 ns (shortest selectable interval) to 1000 ns in 200 ns steps.…”
Section: Measurement Of the Initial Ion Velocitymentioning
confidence: 99%
“…Theoretical investigations predict two desorption mechanisms that occur in MALDI: thermal vaporization of single molecules up to small clusters consisting of up to four molecules and phase explosions with ablation of large clusters at higher laser fluences [26 -28]. It was shown that the process of thermal vaporization of small molecules gets favored by increase of the effective temperature, which is accompanied by lower initial ion velocities [22]. Therefore, the question rose whether higher matrix crystal temperatures caused from smaller crystals accompanied by higher effective analyte temperatures in sublimed matrices cause more efficient thermal vaporization by heating and vaporization of the matrix in a larger volume or increased phase explosions by stronger ablation processes.…”
Section: Initial Ion Velocitymentioning
confidence: 99%
“…Device parameters were set to identical values as given in [17]. For each DE time the average flight time of the protonated analyte ions was determined using data from six individual measurements accumulated of 50 shots each.…”
Section: Measurement Of the Initial Velocity Of Clccamentioning
confidence: 99%
“…High fluorescence quantum yields of laser dyes in the solution and likely solid states may also play a role in efficient energy transfer and soft ionization of derivatized biomolecules since thermal relaxation and decomposition of fluorescent molecules are minimized. Nevertheless, although it likely shares many similarities with the mechanisms of LDI and MALDI [2,19,20,[37][38][39][40], detailed mechanism of FALDI remains to be determined by analyzing structurally diverse fluorescently labeled biomolecules using LDI-MS and fluorescence techniques.…”
Section: Resultsmentioning
confidence: 99%
“…For example, coumarin 510, coumarin 519, and rhodamine isothiocyanate (RITC) have been tested as visible-wavelength MALDI matrices [10,11]. Fluorescent dyes have also been used as dye co-matrices for the analysis of protein samples by visible-wavelength MALDI-MS and the investigation of the mechanism of UV MALDI [18][19][20]. The fluorescent dyes, such as coumarin, can covalently label theamine of lysine residues and the N-termini of peptides and proteins in order to investigate labeled biomolecules in fluorescence-based applications [21].…”
Section: Introductionmentioning
confidence: 99%